The Mystery in Curriculum Development: Coming to Know Ourselves as Teachers and Individuals in the World - Shields, Carmen; Podolski, Adam Garry (Journal of the Canadian Association for Curriculum Studies, 2025)
In this paper, we address mystery in curriculum development in a personal and storied way. We share our belief in the ongoing nature of mystery across time and situation, in the teaching life and beyond, into the worlds we inhabit in our daily lives with others. As self-study narrative researchers over many years, we turn to the work of Michael Connelly and Jean Clandinin, William Pinar, Ted Aoki and Maxine Greene to illustrate our perspective that mystery awaits us as we uncover new meaning in the seminal stories we have lived, and which inform us in present day learning and understanding in an ongoing way. We describe two theories that we utilize to guide our path to unearthing the mystery held in our stories—one is Connelly and Clandinin’s narrative inquiry and the other, Pinar’s currere. Both consider curriculum development to be an ongoing and circular course wherein it is always possible to find new meaning from experiences that can open one to new, present-day worlds, where one can live and share interactions with others.